Pendidikan Karakter pada Crita Cekak dalam Buku Teks Prigel Basa Jawa SMA/SMK/MA Karya Gandung Widaryatmo - Purwanti, Fhita Naurma; Alfiah, Alfiah; Werdiningsih, Yuli Kurniati (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2022)
This research aims to describe character education in the short story in the textbooks of Prigel Basa Jawa SMA/SMK/MA by Gandung Widaryatmo. This research uses qualitative methods and the approach used is a pragmatic approach. The source of this research data is the short story text that is in the textbook Prigel Basa Jawa SMA/SMK/MA by Gandung Widaryatmo. The data of this research are in the form of sentences or paragraphs that contain character education in the short stories in the textbook. There are three forms of character education in the short story text in the PBJ SMA/SMK/MA textbook by Gandung Widaryatmo. The form of character education includes character values in relation to God, oneself, and others. The character value in relation to God, namely religiosity, is implemented by praying to God. Character values in relation to oneself include six variations of values, namely; independent, disciplined, superior and achievers, tough, honest, and responsible. The value of character in relation to others consists of two variations of values, namely empathy, and helping to help. Thus the character value in relation to oneself has a more dominant variation of values in the short story in Gandung Widaryatmo's PBJ SMA/SMA/MA textbooks.